Intracellular events regulating cross-presentation - Cresswell, Peter (Frontiers in Immunology, 2012)
Cross-presentation plays a fundamental role in the induction of CD8-T cell immunity. However, although more than three decades have passed since its discovery, surprisingly little is known about the exact mechanisms involved. Here we give an overview of the components involved at different stages of this process. First, antigens must be internalized into the cross-presenting cell. The involvement of different receptors, method of antigen uptake, and nature of the antigen can influence intracellular trafficking and access to the cross-presentation pathway. Once antigens access the endocytic system, different requirements for endosomal/phagosomal processing arise, such as proteolysis and reduction of disulfide bonds. The majority of cross-presented peptides are generated by proteasomal degradation. Therefore, antigens must cross a membrane barrier in a manner analogous to the fate of misfolded proteins in the endoplasmic reticulum (ER) that are retrotranslocated into the cytosol for degradation. Indeed, some components of the ER-associated degradation machinery have been implicated in cross-presentation. Further complicating the matter, endosomal and phagosomal compartments have been suggested as alternative sites to the ER for loading of peptides on major histocompatibility complex class I molecules. Finally, the antigen presenting cells involved, particularly dendritic cell subsets and their state of maturation, influence the efficiency of cross-presentation.